2016
DOI: 10.1590/0104-6632.20160333s20150107
|View full text |Cite
|
Sign up to set email alerts
|

On the Synthesis of Molybdenum Carbide With Cobalt Addition via Gas-Solid Reactions in a Ch4/H2 Atmosphere

Abstract: -Due to ever more severe environmental regulations regarding SOx, NOx and other pollutants' emissions, there has been an interest in developing new and improved catalysts for hydroprocessing reactions. Mo2C has been reported to display good selectivity and activity for those reactions, especially for HDS. Addition of another metal to the carbide structure may improve catalytic properties. Mo2C with low cobalt addition (2.5 and 5%) was obtained via gas-solid reaction in a fixed bed reactor with CH4 (5%)/H2 atmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…The catalyst was then carburized with a process shown in previous literature. 33,34 The catalyst was carburized on a stainless steel reactor with a capacity for 10 g of catalyst. During the carburization, a flow of 250 ml/min of a mixture containing 20% CH 4 in H 2 was passed through the reactor.…”
Section: Introductionmentioning
confidence: 99%
“…The catalyst was then carburized with a process shown in previous literature. 33,34 The catalyst was carburized on a stainless steel reactor with a capacity for 10 g of catalyst. During the carburization, a flow of 250 ml/min of a mixture containing 20% CH 4 in H 2 was passed through the reactor.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [17] reported that the highest diffraction peak of α-MoO3 appears at 2θ = 27.36°; meanwhile, Sen et al [18] reported that it appears at 2θ = 27.32°. Moreover, new peaks appear at 2θ = 26.5, 27.3, 28.2, 32.2, and 33.8° in the Co-Mo/ZSM-5 catalyst, corresponding to β-CoMoO4 (JCPDS-21-0868) [20][21][22][23]. Based on this analysis, it can be deduced that the metals have been impregnated with the ZSM-5 catalyst due to the appearance of the peaks corresponding to the impregnated metals.…”
Section: Catalysts Characterizationsmentioning
confidence: 80%
“…On the other hand, the peak at 2θ = 27.6 • in ZSM-5 is sharpened/heightened and shifted to 27.4 • due to the presence of the highest corresponding peak of α-MoO 3 . Wang et al [17] reported that the highest diffraction peak of α-MoO 3 appears at 2θ = 27.36 • ; meanwhile, Sen et al [18] reported that it appears at 2θ = 27.32 [20][21][22][23]. Based on this analysis, it can be deduced that the metals have been impregnated with the ZSM-5 catalyst due to the appearance of the peaks corresponding to the impregnated metals.…”
Section: Catalysts Characterizationsmentioning
confidence: 88%
“…Mo 2 C/CNF catalyst also showed a major reflexion intensity at 26 • and a minor peak at 45 • , with both being assigned to the graphitic carbon phase. The same diffractograms also revealed seven small peaks assigned to the molybdenum carbide phase (Mo 2 C), with reflexions detected at 2θ angles of 34 • , 38 • , 40 • , 52 • , 61 • , 69 • , 75 • , and 76 • , assigned to orthorhombic Mo 2 C (lattice parameters a = 0.4724 nm, b = 0.6002 nm, c = 0.5215 nm) [11,[29][30][31][32][33]. The size of the crystallites (interpreted here as coherent diffraction domains) estimated by XRD is ca.…”
Section: Fresh Catalysts Characterizationmentioning
confidence: 99%